The Role of Market Segmentation and Distribution Channel Preferences in Increasing Sales Volume of Purung Tofu Factory, Trenggalek Regency - Mukti, Irfan Hari; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to explore the role of market segmentation and distribution channel preferences in increasing the sales volume of Purung Tofu Factory in Trenggalek Regency. Design/Methods/Approach :. This study used an exploratory qualitative approach with in-depth interview and observation methods. Data were collected from factory owners and consumers through the 5R informant selection technique. Research Finding : The results show that market segmentation based on geographic characteristics, demographics, psychographics, and consumption behavior can help tofu factories identify the main target market. Distribution channel preferences such as traditional markets, modern stores, and direct purchase to factories have an important role in product distribution efficiency and increasing sales volume. The integration of these two aspects has a positive impact on the competitiveness and business sustainability of small-scale tofu factories. Theoretical contribution/Originality : This study offers a theoretical contribution by integrating market segmentation and distribution channel preferences as an integrated approach in the marketing strategy of traditional tofu factories. This study also fills the literature gap regarding the effect of the combination of these two aspects on increasing sales volume in the local business context. Practitioner/Policy implication : The findings of this study can serve as a guide for the managers of Purung Tofu Factory to design a more effective and efficient marketing strategy. In addition, local governments and industry players can use the results of this study to encourage the development of traditional food businesses through policies that support optimal management of market segmentation and distribution. Research limitation : This research is limited to the context of Purung Tofu Factory in Trenggalek Regency, so the results cannot be generalized to tofu factories in other regions. Further studies are needed to test the model developed in tofu factories with different consumer characteristics.